Nonlinear down-conversion in a single quantum dot - Jonas, Björn; Heinze, Dirk Florian; Schöll, Eva; Kallert, Patricia; Langer, Timo; Krehs, Sebastian; Widhalm, Alex; Jöns, Klaus; Reuter, Dirk; Zrenner, Artur

Electron polarons in lithium niobate: Charge localization, lattice deformation, and optical response - Schmidt, Falko; Kozub, Agnieszka L.; Gerstmann, Uwe; Schmidt, Wolf Gero; Schindlmayr, Arno (New Trends in Lithium Niobate: From Bulk to Nanocrystals)
Lithium niobate (LiNbO3), a material frequently used in optical applications, hosts different kinds of polarons that significantly affect many of its physical properties. In this study, a variety of electron polarons, namely free, bound, and bipolarons, are analyzed using first-principles calculations. We perform a full structural optimization based on density-functional theory for selected intrinsic defects with special attention to the role of symmetry-breaking distortions that lower the total energy. The cations hosting the various polarons relax to a different degree, with a larger relaxation corresponding to a larger gap between the defect level and the conduction-band edge. The projected density of states reveals that the polaron states are formerly empty Nb 4d states lowered into the band gap. Optical absorption spectra are derived within the independent-particle approximation, corrected by the GW approximation that yields a wider band gap and by including excitonic effects within the Bethe-Salpeter equation. Comparing the calculated spectra with the density of states, we find that the defect peak observed in the optical absorption stems from transitions between the defect level and a continuum of empty Nb 4d states. Signatures of polarons are further analyzed in the reflectivity and other experimentally measurable optical coefficients.

Bound polaron formation in lithium niobate from ab initio molecular dynamics - Krenz, Marvin; Gerstmann, Uwe; Schmidt, Wolf Gero (Applied Physics A)
Abstract Polarons influence decisively the performance of lithium niobate for optical applications. In this work, the formation of (defect) bound polarons in lithium niobate is studied by ab initio molecular dynamics. The calculations show a broad scatter of polaron formation times. Rising temperature increases the share of trajectories with long formation times, which leads to an overall increase of the average formation time with temperature. However, even at elevated temperatures, the average formation time does not exceed the value of 100 femtoseconds, i.e., a value close to the time measured for free, i.e., self-trapped polarons. Analyzing individual trajectories, it is found that the time required for the structural relaxation of the polarons depends sensitively on the excitation of the lithium niobate high-frequency phonon modes and their phase relation.
Keywords: General Materials Science; General Chemistry

Two-Mode Photon-Number Correlations Created by Measurement-Induced Nonlinearity - Meier, Torsten; Hoepker, Jan Philipp; Protte, Maximilian; Eigner, Christof; Silberhorn, Christine; Sharapova, Polina R.; Sperling, Jan; Bartley, Tim (Conference on Lasers and Electro-Optics: Applications and Technology)
We demonstrate theoretically and experimentally complex correlations in the photon numbers of two-mode quantum states using measurement-induced nonlinearity. For this, we combine the interference of coherent states and single photons with photon sub-traction.

DC Ionic Conductivity in KTP and Its Isomorphs: Properties, Methods for Suppression, and Its Connection to Gray Tracking - Padberg, Laura; Quiring, Viktor; Bocchini, Adriana; Santandrea, Matteo; Gerstmann, Uwe; Schmidt, Wolf Gero; Silberhorn, Christine; Eigner, Christof (Crystals)
We study the DC conductivity in potassium titanyl phosphate (KTiOPO4, KTP) and its isomorphs KTiOAsO4 (KTA) and Rb1%K99%TiOPO4 (RKTP) and introduce a method by which to reduce the overall ionic conductivity in KTP by a potassium nitrate treatment. Furthermore, we create so-called gray tracking in KTP and investigate the ionic conductivity in theses areas. A local unintended reduction of the ionic conductivity is observed in the gray-tracked regions, which also induce additional optical absorption in the material. We show that a thermal treatment in an oxygen-rich atmosphere removes the gray tracking and brings the ionic conductivity as well as the optical transmission back to the original level. These studies can help to choose the best material and treatment for specific applications.

Flexible source of correlated photons based on LNOI rib waveguides - Ebers, Lena; Ferreri, Alessandro; Hammer, Manfred; Albert, Maximilian; Meier, Cedrik; Förstner, Jens; Sharapova, Polina R. (Journal of Physics: Photonics)
Lithium niobate on insulator (LNOI) has a great potential for photonic integrated circuits, providing substantial versatility in design of various integrated components. To properly use these components in the implementation of different quantum protocols, photons with different properties are required. In this paper, we theoretically demonstrate a flexible source of correlated photons built on the LNOI waveguide of a special geometry. This source is based on the parametric down-conversion (PDC) process, in which the signal and idler photons are generated at the telecom wavelength and have different spatial profiles and polarizations, but the same group velocities. Distinguishability in polarizations and spatial profiles facilitates the routing and manipulating individual photons, while the equality of their group velocities leads to the absence of temporal walk-off between photons. We show how the spectral properties of the generated photons and the number of their frequency modes can be controlled depending on the pump characteristics and the waveguide length. Finally, we discuss special regimes, in which narrowband light with strong frequency correlations and polarization-entangled Bell states are generated at the telecom wavelength.
Keywords: tet_topic_waveguide

Quasiparticle energies and optical response of RbTiOPO4 and KTiOAsO4 - Neufeld, Sergej; Schindlmayr, Arno; Schmidt, Wolf Gero (Journal of Physics: Materials)
Many-body perturbation theory based on density-functional theory calculations is used to determine the quasiparticle band structures and the dielectric functions of the isomorphic ferroelectrics rubidium titanyl phosphate (RbTiOPO4) and potassium titanyl arsenide (KTiOAsO4). Self-energy corrections of more than 2 eV are found to widen the transport band gaps of both materials considerably to 5.3 and 5.2 eV, respectively. At the same time, both materials are characterized by strong exciton binding energies of 1.4 and 1.5 eV, respectively. The solution of the Bethe-Salpeter equation based on the quasiparticle energies results in onsets of the optical absorption within the range of the measured data.

Clean and Hydrogen‐Adsorbed AlInP(001) Surfaces: Structures and Electronic Properties - Glahn, Luis Joel; Ruiz Alvarado, Isaac Azahel; Neufeld, Sergej; Zare Pour, Mohammad Amin; Paszuk, Agnieszka; Ostheimer, David; Shekarabi, Sahar; Romanyuk, Oleksandr; Moritz, Dominik Christian; Hofmann, Jan Philipp; Jaegermann, Wolfram; Hannappel, Thomas; et al. (physica status solidi (b))
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Water/InP(001) from Density Functional Theory - Ruiz Alvarado, Isaac Azahel; Schmidt, Wolf Gero (ACS Omega)
Keywords: General Chemical Engineering; General Chemistry

P-Terminated InP (001) Surfaces: Surface Band Bending and Reactivity to Water - Moritz, Dominik Christian; Ruiz Alvarado, Isaac Azahel; Zare Pour, Mohammad Amin; Paszuk, Agnieszka; Frieß, Tilo; Runge, Erich; Hofmann, Jan P.; Hannappel, Thomas; Schmidt, Wolf Gero; Jaegermann, Wolfram (ACS Applied Materials & Interfaces)
Keywords: General Materials Science

Reconstructions of the As-Terminated GaAs(001) Surface Exposed to Atomic Hydrogen - Karmo, Marsel; Ruiz Alvarado, Isaac Azahel; Schmidt, Wolf Gero; Runge, Erich (ACS Omega)
Keywords: General Chemical Engineering; General Chemistry

Programmierung und Computersimulationen - Schindlmayr, Arno (Kompetent Prüfungen gestalten: 60 Prüfungsformate für die Hochschullehre)
Dieses Format eignet sich, um zu prüfen, inwieweit Studierende Computersimulationen und eigene kleine Programme zur Lösung typischer Probleme ihres Fachs nutzen können. Wie bei Klausuren erfolgt die Bearbeitung in begrenzter Zeit und unter Aufsicht, wird aber am Computer durchgeführt und beinhaltet neben der Programmierung auch vor- und nachbereitende Aufgaben im Kontext der fachlichen Anwendung.

Direct Measurement of Higher-Order Nonlinear Polarization Squeezing - Prasannan, Nidhin; Sperling, Jan; Brecht, Benjamin; Silberhorn, Christine (Physical Review Letters)
Keywords: General Physics and Astronomy

Protonation-induced charge transfer and polaron formation in organic semiconductors doped by Lewis acids - Bauch, Fabian; Dong, Chuan-Ding; Schumacher, Stefan (RSC Advances)
Lewis-acid doping of organic semiconductors (OSCs) opens up new ways of p-type doping and has recently become of significant interest.
Keywords: General Chemical Engineering; General Chemistry

Tilting nondispersive bands in an empty microcavity - Gao, Ying; Li, Yao; Ma, Xuekai; Gao, Meini; Dai, Haitao; Schumacher, Stefan; Gao, Tingge (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Microscopic Study of Molecular Double Doping - Bathe, Thomas; Dong, Chuan-Ding; Schumacher, Stefan (The Journal of Physical Chemistry A)
Keywords: Physical and Theoretical Chemistry

Electron–Nuclear Coherent Coupling and Nuclear Spin Readout through Optically Polarized VB– Spin States in hBN - Murzakhanov, Fadis F.; Mamin, Georgy Vladimirovich; Orlinskii, Sergei Borisovich; Gerstmann, Uwe; Schmidt, Wolf Gero; Biktagirov, Timur; Aharonovich, Igor; Gottscholl, Andreas; Sperlich, Andreas; Dyakonov, Vladimir; Soltamov, Victor A. (Nano Letters)
Keywords: Mechanical Engineering; Condensed Matter Physics; General Materials Science; General Chemistry; Bioengineering

Electrochemical performance of KTiOAsO_4 (KTA) in potassium-ion batteries from density-functional theory - Bocchini, Adriana; Gerstmann, Uwe; Bartley, Tim; Steinrück, Hans-Georg; Henkel, Gerald; Schmidt, Wolf Gero (Phys. Rev. Materials)

Oxygen vacancies in KTiOPO_4: Optical absorption from hybrid DFT - Bocchini, Adriana; Gerstmann, Uwe; Schmidt, Wolf Gero (Phys. Rev. B)

Driven Gaussian quantum walks - Held, Philip; Engelkemeier, Melanie; De, Syamsundar; Barkhofen, Sonja; Sperling, Jan; Silberhorn, Christine (Physical Review A)
Quantum walks function as essential means to implement quantum simulators, allowing one to study complex and often directly inaccessible quantum processes in controllable systems. In this contribution, the notion of a driven Gaussian quantum walk is introduced. In contrast to typically considered quantum walks in optical settings, we describe the operation of the walk in terms of a nonlinear map rather than a unitary operation, e.g., by replacing a beam-splitter-type coin with a two-mode squeezer, being a process that is controlled and driven by a pump field. This opens previously unattainable possibilities for quantum walks that include nonlinear elements as core components of their operation, vastly extending their range of applications. A full framework for driven Gaussian quantum walks is developed, including methods to dynamically characterize nonlinear, quantum, and quantum-nonlinear effects. Moreover, driven Gaussian quantum walks are compared with their classically interfering and linear counterparts, which are based on classical coherence of light rather than quantum superpositions. In particular, the generation and boost of highly multimode entanglement, squeezing, and other quantum effects are studied over the duration of the nonlinear walk. Importantly, we prove the quantumness of the evolution itself, regardless of the input state. A scheme for an experimental realization is proposed. Furthermore, nonlinear properties of driven Gaussian quantum walks are explored, such as amplification that leads to an ever increasing number of correlated quantum particles, constituting a source of new walkers during the walk. Therefore, a concept for quantum walks is proposed that leads to—and even produces—directly accessible quantum phenomena, and that renders the quantum simulation of nonlinear processes possible.